Optimization Method for Computing Radial Gravity Gradient Using Gravity Gradient Observations - MENG Xiangchao (Acta Geodaetica et Cartographica Sinica, 2016)
This paper proposes an optimization method for computing the radial gravity gradient by using GOCE gradient measurements, based on the variance-covariance information of gradient observations. The approach for computing the gravity gradient and the error propagation are firstly discussed; and then by solving a conditional extremum problem, we can get an optimal combination factor which can improve the calculation accuracy for the radial gravity gradient. The advantage of the combination factor is validated by simulation data. In actual data processing, the geoid accuracy truncated to degree 250 can be improved by 2 cm by using the optimization method. The radial gravity gradient can not only be used in recovering a gravity field model, but also can be used in kinds of geophysical interpretation, so the method provided in the paper can be helpful in the related researches.